Comparative Analysis of Edge Feeding and coaxial Feeding Technique with Fixed Frequency - S. Mohan Reddy, S; Vinod Kumar, M; Sanjay, B; Aruna Kumari, K (International Journal of Engineering and Technology, 2018)
The performance of rectangular microstrip patch antenna with the edge feeding and coaxial feeding techniques with DGS (Defective ground structure) and DSS (Defective substrate structure) are analyzed. It was observed that the return loss for Edge feeding is -28.39dB, for DSS it is - 26.44 and return loss for coaxial with DGS is -27.50dB and for DSS is -28.52. VSWR is approximately equal to 1 for all designs and also it was observed that the Gain is enhancement in Edge feeding and Bandwidth is improvement with coaxial feeding. The antenna designing and simulation is done by using the ANSOFT HFSS Software.Â Â